2012
DOI: 10.1016/j.cyto.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ, tumor necrosis factor, and interleukin-18 cooperate to control growth of Mycobacterium tuberculosis in human macrophages

Abstract: Mycobacterium tuberculosis (MTB) remains a leading infectious threat to human health. Macrophages are the cells targeted for infection by the bacterium as well as key effector cells for clearance of the pathogen. Interleukin (IL)-27 opposes macrophage-mediated control of MTB because supplying IL-12 and blocking the activity of IL-27 limits bacterial growth in primary human macrophages. The purpose of this study was to determine the immunological regulators of this macrophage mechanism to restrict MTB growth. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 29 publications
3
66
0
1
Order By: Relevance
“…Increased lymphocytic character of TB granuloma and decrease in bacterial number were observed in IL-27R knockout mice (Pearl et al, 2004). Robinson et al (2012) reported that neutralization of IL-27 enhances mycobacterial clearance in infected human macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…Increased lymphocytic character of TB granuloma and decrease in bacterial number were observed in IL-27R knockout mice (Pearl et al, 2004). Robinson et al (2012) reported that neutralization of IL-27 enhances mycobacterial clearance in infected human macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…Our data showed that ficolin-2 stimulated macrophages to produce high levels of IFN-γ, TNF-α, and NO, indicating that ficolin-2 might activate M1 macrophages (characteristic of Th1-type immunity), therefore stimulating cell-mediated responses that play major roles in the defense against intracellular pathogens [38]. Robinson et al [39] showed that IFN-γ, TNF-α, and interleukin (IL)-18 cooperated to control the growth of Mtb in human macrophages. Several recent reports demonstrated that IL-17A increased protection against Mtb infection [40].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated constitutive arginase-1 protein expression in unstimulated human macrophages (37). A competition for pools of available substrate could curtail NO production.…”
Section: Resultsmentioning
confidence: 99%